2007
DOI: 10.1016/j.bone.2007.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Letter re: “The 3.6 kb DNA fragment from the rat Col1a1 gene promoter drives the expression of genes in both osteoblast and osteoclast lineage cells” by Boban et al. (Bone 39:1302–1312, 2006)

Abstract: In the paper by Boban and colleagues [1], the authors used a parabiosis mouse model to test whether osteoblast-lineage cells traversed the circulation of the parabiosed pair. Using mice expressing GFP driven by the col3.6 promoter, they found that there were GFP-positive cells lining bone surfaces in the non-GFP-expressing parabiosed mouse, indicating extensive transfer of GFP-positive cells. In addition, when they infused Lin − Sca-1 + c-kit + cells from a col3.6-GFP mouse into a non-GFP-expressing mouse, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The Col3.6 promoter has been reported to direct very low level expression of a GFP transgene in the osteoclast lineage [33], although some of these cells may be bone lining cells [34]. Some studies have reported that glucocorticoids exert direct effects on osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…The Col3.6 promoter has been reported to direct very low level expression of a GFP transgene in the osteoclast lineage [33], although some of these cells may be bone lining cells [34]. Some studies have reported that glucocorticoids exert direct effects on osteoclasts.…”
Section: Discussionmentioning
confidence: 99%